2010
DOI: 10.1175/2010jhm1207.1
|View full text |Cite
|
Sign up to set email alerts
|

Parameterization of Lakes and Wetlands for Energy and Water Balance Studies in the Great Lakes Region*

Abstract: Lakes and wetlands are prevalent around the Great Lakes and play an important role in the regional water and energy cycle. However, simulating their impacts on regional-scale hydrology is still a major challenge and not widely attempted. In the present study, the Variable Infiltration Capacity (VIC) model is applied and evaluated with a physically based lake and wetland algorithm, which can simulate the effect of lakes and wetlands on the grid cell energy and water balance. The VIC model was calibrated at 10 U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
34
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(41 citation statements)
references
References 59 publications
(80 reference statements)
4
34
0
Order By: Relevance
“…They are commonly expected to regulate river flow, mitigate flood events and recharge groundwater. These observations are consistent with a modelling study by Mishra et al (2010) who found decreased surface runoff in wetland dominated regions. However, a number of studies exists that describe the opposite behaviour (Bullock and Acreman, 2003).…”
Section: T Stacke and S Hagemann: The Dynamical Wetland Schemesupporting
confidence: 93%
See 1 more Smart Citation
“…They are commonly expected to regulate river flow, mitigate flood events and recharge groundwater. These observations are consistent with a modelling study by Mishra et al (2010) who found decreased surface runoff in wetland dominated regions. However, a number of studies exists that describe the opposite behaviour (Bullock and Acreman, 2003).…”
Section: T Stacke and S Hagemann: The Dynamical Wetland Schemesupporting
confidence: 93%
“…The effect of open water surfaces on the energy and water balance was investigated by several modelling studies, e.g. Bonan (1995) and Mishra et al (2010), who reported a significant impact of wetlands on the local climate. Generally, they found a cooling of the surface temperature in wetland dominated regions due to increased evapotranspiration (ET), as well as an increase in the latent heat flux and a decrease in the sensible heat flux.…”
Section: T Stacke and S Hagemann: The Dynamical Wetland Schemementioning
confidence: 99%
“…The Variable Infiltration Capacity (VIC) hydrology model (Liang et al 1994,1996, Bowling and Lettenmaier 2010, Mishra et al 2010 (Saurral et al 2008, Su and Lettenmaier 2009, Saurral 2010) and the Iberá wetlands , Grimson et al 2013). …”
Section: The Hydrology Modelmentioning
confidence: 99%
“…In the study region, many inland lakes of relatively smaller size than that of Great Lakes are present. The size of lakes included in this study vary from 0.01 to 557 km 2 while the depth of lakes vary from 0.3 to 91.4 m as described in Mishra et al (2010). Seasonal lake ice forms on all lakes in the region, with the number of ice-free days ranging from 140 in the north to 230 in the south (Magnuson et al, 1997).…”
Section: Study Regionmentioning
confidence: 99%
“…Six parameters related to infiltration, runoff and baseflow generation were adjusted during the model calibration (as described in Mishra et al, 2010), while other variables not available from the CONUS-SOIL dataset were set to the default values used for the VIC model within the Land Data Assimilation System (LDAS) (Maurer et al, 2002).…”
Section: Soil and Land Cover Datamentioning
confidence: 99%